1977
DOI: 10.1172/jci108895
|View full text |Cite
|
Sign up to set email alerts
|

Study of factors causing excess protoporphyrin accumulation in cultured skin fibroblasts from patients with protoporphyria.

Abstract: A B S T R A C T The activity of heme synthetase, which catalyzes the chelation offerrous iron to protoporphyrin to form heme, is deficient in sonicates of skin fibroblasts cultured from patients with protoporphyria. During culture in Eagle's medium supplemented with fetal calf serum, these cells do not accumulate protoporphyrin, however. This may be due to a minimal re quirement for heme synthesis, since glycine is incorporated into heme at a low rate which is similar to that in normal fibroblasts. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 27 publications
3
25
0
Order By: Relevance
“…SC). A similar effect of added iron has been reported in cultured skin fibroblasts from EPP patients (10). However, when EPP lymphocytes were treated with iron in addition to ALA there was no detectable difference in protoporphyrin IX concentrations (Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…SC). A similar effect of added iron has been reported in cultured skin fibroblasts from EPP patients (10). However, when EPP lymphocytes were treated with iron in addition to ALA there was no detectable difference in protoporphyrin IX concentrations (Fig.…”
Section: Resultssupporting
confidence: 83%
“…This finding strongly suggests that ferrochelatase activity in lymphocytes from patients with EPP as determined in the intact cell is functionally deficient and is only -50% that of normal cells. Similar findings of excess protoporphyrin IX accumulation from added ALA have been reported in skin fibroblast cultures from patients with EPP (10) and from cattle with an autosomal recessive form of EPP (6). Our previous studies have shown that the iron chelator CaMgEDTA is an inhibitor of ferrochelatase in cultured chick embryo hepatocytes (7), chick embryo dorsal root ganglion cells (11,12), and bovine skin fibroblasts (6).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Protoporphyria is an inherited disorder of porphyrin metabolism in which deficiency of heme synthase leads to overproduction of protoporphyrin (1)(2)(3)(4)(5). The initial manifestation and dominant symptom of the disorder is a photodermatitis characterized by erythema, edema and pain (1,6,7).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, EPP is thought to be an autosomal dominant disease, but the frequency of its clinical expression is highly variable (2). Previous studies have shown that, in patients with EPP, the activity of ferrochelatase (protoheme ferro-lyase, EC 4.99.1.1) is decreased to -50% compared with normal levels, in all tissues and isolated cell preparations so far examined: e.g., bone marrow (3), liver (4), cultured skin fibroblasts (5), and lymphoblasts (6). A deficiency of ferrochelatase activity is consistent with the marked increase in protoporphyrin IX, a substrate for the enzyme, observed in erythrocytes, plasma, and liver of patients with EPP, and accounts for cutaneous photosensitivity in this disorder.…”
mentioning
confidence: 99%